A new genus and four new species of dactylogyrids (Monogenea), gill parasites of pimelodid catfishes (Siluriformes: Pimelodidae) in South America and the reassignment of Urocleidoides megorchis Mizelle et Kritsky, 1969 - Acosta, Aline A. [UNESP]; Mendoza-Palmero, Carlos A.; da Silva, Reinaldo J. [UNESP]; Scholz, Tomas (Biology Centre, AS CR, 2019)
Nanayella gen. n. is proposed to accommodate four new species of dactylogyrid monogeneans found on the gills of two species of pimelodid catfishes (Siluriformes) from the Amazon River basin in Peru and the Upper Paraná River basin in Brazil. Nanayella gen. n. is mainly characterised by the presence of modified hook pairs 5 and 6, which have a slender shank with slightly enlarged base, inconspicuous thumb, and straight point. Nanayella aculeatrium gen. n. et sp. n. (type species) from Sorubim lima (Bloch et Schneider) (type host) differs from its congeners mainly by possessing seven sclerotised spines on one side of circular ornamentation of the vaginal atrium. Nanayella fluctuatrium gen. n. et sp. n. is characterised by the presence of sclerotised undulations surrounding the circular ornamentation of the vaginal atrium. Nanayella amplofalcis gen. n. et sp. n. is typified by possessing hook pairs 1 and 2 with a robust, wide shank and a round, weakly sclerotised subunit at the base. Nanayella processusclavis gen. n. et sp. n. differs from congeners by the presence of a conspicuous posterior medial process on the dorsal bar. Urocleidoides megorchis Mizelle et Kritsky, 1969 described from the gills of S. lima in Brazil is transferred to Nanayella gen. n. as Nanayella megorchis comb. n. based on morphological and molecular evidence. Analyses of partial sequences of the 28S rRNA gene revealed all five species of the new genus to form a monophyletic clade within a bigger clade comprised of dactylogyrids of South American pimelodids.
Keywords: 28S rRNA; Ancyrocephalinae; integrative taxonomy; morphology; Neotropical regionThis article contains supporting information (S1-S2) online at http://folia.paru.cas.cz/suppl/2019-66-004.pdf; Sorubiminae